Level of Knowledge of Basic Life Support (BLS) in Final Students of Diploma 3 Nursing Study Program in Indonesia - Luthfia Rizqy, Kiki; Okviasanti, Fanni; Harianto, Susilo; Rahmadi Purwanto, Cucuk; Ilmy Muhalla, Hafna; Rindayati, Rindayati (Kirana Publisher (KNPub), 2025)
Emergency cases requiring basic life support (BLS) are often found in the Emergency Department. Knowledge of BLS is very important for students, especially in the final year who are doing internships in hospitals. The purpose of this study was to describe the level of knowledge of BLS in final year students of the Diploma 3 Nursing Study Program in Indonesia. This study used a descriptive research design with a quantitative approach. The sample of this study was 203 students taken using the cluster random sampling technique. The research variable was the level of knowledge of BLS. The research instrument was a knowledge questionnaire. Data analysis used univariate analysis in the form of frequency distribution and percentage. The results showed that most students in Indonesia had a good level of knowledge of BLS of 73.8%. Regular simulations and exercises are expected to increase the confidence of students who already have good knowledge in carrying out BLS.